Notes de recherche: Le mythe comme objet technique - Simonis, Yvan (Anthropologica, 2022)
Myths, as viewed through Levi-Strauss’ structural analysis, seem to present characteristics analogous with those of "technical objects" according to Simondon. In this note, the author compares sketchily Levi-Strauss’ and Simondon’s theoretical propositions. He suggests to carry the comparison further in order to clarify the theoretical discourse implied in the structural analysis of myths.